Artemis Fowl : the graphic novel - Colfer, Eoin; Moreci, Michael (Disney/Hyperion, 2019)
When a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold, the fairies fight back with magic, technology, and a particularly nasty troll.